2020
DOI: 10.1371/journal.pone.0228396
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of peripheral venous catheter-associated gram-negative bloodstream infection among patients with malignancy

Abstract: Previous studies have suggested that peripheral venous catheter is a significant source of gram-negative bacteraemia in patients with malignancy. We aimed to identify risk factors and develop a clinical prediction rule for the involvement of gram-negative organisms in peripheral venous catheter-associated bloodstream infections (PVC-BSIs) among patients with malignancy. Methods This retrospective cohort study was conducted at a 700-bed cancer hospital in Japan. Consecutive patients diagnosed with PVC-BSI based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Recent studies have addressed PIVC-related practices and outcomes in adult oncology patients, focusing on the identification of inherent and modifiable risk factors for PIVC difficulty and failure, mostly through single-day data collection methods or via secondary analysis [5,[8][9][10][11]. Other authors have explored nurses' knowledge, confidence levels, and adherence to local policies in this field [6,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have addressed PIVC-related practices and outcomes in adult oncology patients, focusing on the identification of inherent and modifiable risk factors for PIVC difficulty and failure, mostly through single-day data collection methods or via secondary analysis [5,[8][9][10][11]. Other authors have explored nurses' knowledge, confidence levels, and adherence to local policies in this field [6,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In oncology units, the recent cumulative incidence of extravasation with PIVC was reported to be 0.09% (Jackson-Rose et al, 2017), and another single-center study revealed that 4.9% of cases required surgery and 3.3% required direct wound closure for skin necrosis due to extravasation (Onesti et al, 2017), although these results are combined central venous catheters (CVCs) and PIVCs. Also, blood stream infections (BSI) may occur, which are potentially life-threatening under myelosuppression (Austin et al, 2016;Sasaki et al, 2020). Therefore, PIVC failure in cancer patients may lead not only to reinsertion but also to treatment delays for cancer due to intensive treatments, such as plastic surgery of skin for severe necrosis, or due to antimicrobial administration to treat infection.…”
Section: Introductionmentioning
confidence: 99%
“…The above reasons can cause the interruption of treatments that is harmful to patients. Moreover, PVC replacement causes pain on patients and increases treatment costs [58]. A biodegradable water absorption sponge incorporating AgNP had antibacterial properties [59].…”
Section: Discussionmentioning
confidence: 99%